2018
DOI: 10.1128/mbio.02430-18
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei PRMT1 Is a Nucleic Acid Binding Protein with a Role in Energy Metabolism and the Starvation Stress Response

Abstract: Trypanosoma brucei infection causes human African trypanosomiasis, also known as sleeping sickness, a disease with a nearly 100% fatality rate when untreated. Current drugs are expensive, toxic, and highly impractical to administer, prompting the community to explore various unique aspects of T. brucei biology in search of better treatments. In this study, we identified the protein arginine methyltransferase (PRMT), TbPRMT1, as a factor that modulates numerous aspects of T. brucei biology. These include glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 72 publications
(107 reference statements)
2
23
0
Order By: Relevance
“…Recent studies have shown that nutrient deprivation could activate SG formation in cells, yeast, and the single‐celled organism, T. crucei (Kafkova et al., 2018). To investigate whether starvation or dietary restriction could induce stress granule formation in C. elegans , TIAR‐1::GFP knock‐in animals at L3 stages were transferred to foodless plates for two hours and SG formation was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that nutrient deprivation could activate SG formation in cells, yeast, and the single‐celled organism, T. crucei (Kafkova et al., 2018). To investigate whether starvation or dietary restriction could induce stress granule formation in C. elegans , TIAR‐1::GFP knock‐in animals at L3 stages were transferred to foodless plates for two hours and SG formation was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Data indicate that this reprogramming involves mainly degradation of organelles containing the redundant enzyme repertoire by pexophagy-i.e., the autophagy process characteristic for peroxisome degradation-while new organelles are formed with an enzyme content that is appropriate for the conditions to be encountered by the new developmental form. Glycosomal proteins are encoded by genes in the nucleus and regulation of the glycosomal enzyme content is thought to occur via mechanisms controlling both expression of genes in general and that of genes for metabolic enzymes in particular in trypanosomes, i.e., mainly post-transcriptionally (Kafková et al, 2018;Clayton, 2019). Furthermore, it is feasible that the relative abundance of different proteins in the organelles is also dependent on differential rates of their import, since the sequence motif variants of PTS exhibit different import efficiencies (Sommer et al, 1992).…”
Section: Glycosomal Reprogramming During Differentiation Of Trypanosomesmentioning
confidence: 99%
“…PRMTs have previously been shown to regulate the RNA affinity of target RBPs in other systems (55,56). In T. brucei, the RNA-binding proteins DRBD18 and PRMT1 have been shown to modulate the fate of mRNAs according to methylation state, impacting both protein and mRNA binding (45,50). Here we dissect the effect of MMA upon RNA affinity and isolate the specific arginines of Alba3 that are monomethylated by PRMT7; resulting in the discrete maintenance or loss of specific transcript targets.…”
Section: Discussionmentioning
confidence: 93%
“…indicative of a complex PRMT inter-regulatory system. Deletion of mammalian PRMT1, which catalyzes asymmetric dimethylarginine (ADMA), results in an increase of global MMA in mammals and T.brucei (44,45). Therefore, functional overlap between Leishmania PRMTs may involve a dynamic regulatory interplay as it does in T.brucei (46).…”
Section: Discussionmentioning
confidence: 99%